Cardiac arrest caused by the application of pituitrin during laparoscopic myomectomy - Jia-Rui Li; Xin Liao; Feng-Qiong Lv; Hui Li (BMC, 2023)
Abstract Background Pituitrin injection solution is an indispensable hemostatic utilized in clinical practice and is widely used in myomectomy. However, there have been reports of adverse reactions leading to gastrointestinal injury, hyponatremia and hypokalemia, anaphylaxis, cardiac arrest, etc. Thus, the safety of pituitrin should be taken seriously. Case presentation In the present study, three cases of cardiac arrest caused by pituitrin injection during laparoscopic myomectomy, who were successfully resuscitated in our hospital, are reported. Conclusion The clinical data and surgical procedures in the patient should be analyzed to find the causes of cardiac arrest. Medication and resuscitation should be summarized to ensure the safety of the patient.